KAJIAN PERENCANAAN WILAYAH KEPULAUAN DALAM INTERPRETASI HUKUM DAN ADMINISTRASI PERENCANAAN WILAYAH - Ronaldy Lovina (Karimun University, 2022)
Abstract Regional spatial management is regulated as a guideline in preparing a synchronous and integrated sustainable development program between planning documents. The Planning Documents can be in the form of Regional and City Planning Documents as well as Zoning Planning Documents for Water Areas and Small Islands, in addition to being included in documents that regulate development program plans such as Long-Term, Medium-Term Development Planning Documents and Work Plans for each Instasi/ Institution. In the preparation of the Planning Document whose output is in the form of laws and regulations, namely in the form of Government Regulations, Presidential Regulations and Regional Regulations. The preparation of the Planning Document and its legalization process is guided by the law and planning administration. The existing planning administration law has provided room for movement and guidelines that can provide direction in making a decision on the content of regional planning documents (space, land and sea). After understanding the legislation which is a regional planning law, the author wants to analyze and examine its substance. Keywords: Legal; Administration; Regional; Planning Abstrak Pengelolaan ruang kawasan diatur sebagai pedoman di dalam menyusun program pembangunan yang berkelanjutan yang sinkron dan terintegrasi antar-inter dokumen perencanaan. Dokumen perencanaan tersebut dapat berupa, dokumen perencanaan wilayah dan kota serta dokumen perencanaan zonasi wilayah perairan dan pulau-pulau kecil, selain itu termasuk ke dalam dokumen yang mengatur rencana program pembangunan seperti dokumen perencanaan pembangunan jangka panjang, menengah dan rencana kerja pada masing-masing Instasi/Lembaga. Didalam penyusunan dokumen perencanaan yang outputnya berupa peraturan perundangan yakni berupa peraturan pemerintah , peraturan presiden maupun peraturan daerah. Penyusunan Dokumen Perencanaan dan proses legalisasinya berpedoman kepada hukum dan administrasi perencanaan. Hukum adminsitrasi perencanaan yang ada telah memberikan ruang gerak dan pedoman yang dapat memberikan arahan di dalam membuat suatu keputusan tentang muatan dokumen perencanaan wilayah (ruang, darat dan laut). Setelah memahami peraturan perundangan yang merupakan hukum perencanaan wilayah, penulis ingin menganalisis dan mengkaji substansinya. Kata Kunci: Hukum, Administrasi, Perencanaan, Wilayah, Kepulauan